Volatolomics in Bacterial Ecotoxicology, A Novel Method for Detecting Signatures of Pesticide Exposure? - Hidalgo, Kevin; Ratel, Jeremy; Mercier, Frederic; Gauriat, Benedicte; Bouchard, Philippe; Engel, Erwan (Frontiers in Microbiology, 2019)
Volatile organic compounds ( VOC) produced by microorganisms in response to chemical stressor showed recent increasing attention, because of possible environmental applications. In this work, we aimed to bring the first proof of concept that volatolomic (i.e. VOCs analysis) can be used to determine candidate VOC markers of two soil bacteria strains (Pseudomonas fluorescens SG-1 and Bacillus megaterium Mes11) exposure to pesticides. A solid-phase microextraction (SPME) method coupled with gas chromatography-mass spectrometry (GC-MS) was adapted from a previous works led on livestocks and human gut microbiota. Accordingly, we highlighted a set of bacterial VOCs modulated in each strains according to the nature of the pesticide used. Three out these VOCs were specifically modulated in P. fluorescens SG-1 when exposed with two pyrethroid pesticides (deltamethrine and cypermethrine): 2-hexanone; 1,3-ditertbutylbenzene and malonic acid, hexyl 3-methylbutyl ester. Our results thus suggest the possible existence of generic VOC markers of pyrethroids in this strain. Of particular interest, the 1,3-ditertbutylbenzene and the malonic acid, hexyl 3-methylbutyl ester were found also in B. megaterium Mes11 when exposed with cypermethrine. This result highlighted the possible existence of interspecific VOC markers of pyrethroid in these two bacteria. Altogether, our work underlined the relevance of volatolomic to detect signatures of pesticides exposure in microorganisms and more generally to microbial ecotoxicology.